Relationship between Anxiety Level and Quality Life in Chronic Kidney Disease Patients Undergoing Hemodialysis Therapy at RSUD Lakipadada - Margaretha Rante Musu; Hayuti Windha Pagiu; Nurhikma Bakri (International Journal of Health and Social Behavior, 2025)
Chronic Kidney Disease (CKD) or chronic kidney failure is a condition that occurs due to a decrease in the kidney's ability to maintain balance in the body so that hemodialysis therapy is needed to replace the kidney function. Hemodialysis therapy can cause various physical effects and mental conditions of patients so that it can affect the patient's quality of life. Objective : to determine the relationship between anxiety levels and quality of life of CKD patients undergoing hemodialysis at Lakipada Hospital. Research Method : the research design used is quantitative research with a Cross Sectional approach, using a " saturated sampling" sampling technique with a sample size of 40 respondents. The independent variable is the level of anxiety and the dependent variable is the quality of life. Data were analyzed using the Chi-Square statistical test at a significance level of α <0.05. Research Results : it was found that there was a relationship between anxiety levels and quality of life in CKD patients undergoing hemodialysis with a p-value = 0.000. Conclusion : there is a relationship between anxiety levels and quality of life in CKD patients undergoing hemodialysis.